2016
DOI: 10.1002/ejp.865
|View full text |Cite
|
Sign up to set email alerts
|

D1‐ and D2‐like dopamine receptors within the nucleus accumbens contribute to stress‐induced analgesia in formalin‐related pain behaviours in rats

Abstract: Forced swim stress (FSS) induces the antinociception in both phases of formalin test. Blockade of accumbal dopamine receptors attenuate the antinociception induced by FSS. Stress-induced analgesia is dose-dependently reduced by dopamine receptor antagonists in both phases, although it is more prominent during the late phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Electrophysiological and neuroanatomical evidence has also shown that distinct populations of NAc neurons differentially encode information about goal-directed behaviors for natural (food/water) and cocaine reinforcement (Carelli et al, 2000; Carelli and Wondolowski, 2003; Carelli and Wondolowski, 2006; Castro et al, 2015), while selected neuronal subpopulations of the NAc in the monkey are differently activated by cocaine and juice rewards (Bowman et al, 1996; Hutsell et al, 2016). All these data suggest that there are different and parallel microcircuits mediating the natural and drug-rewarding effects in the NAc (Alizamini et al, 2017; Faramarzi et al, 2016), although the relevant neurotransmitters have not been identified. Our results are consistent with the view that there are distinct neuronal populations within the NAc that mediate seeking behaviors for natural and drug rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological and neuroanatomical evidence has also shown that distinct populations of NAc neurons differentially encode information about goal-directed behaviors for natural (food/water) and cocaine reinforcement (Carelli et al, 2000; Carelli and Wondolowski, 2003; Carelli and Wondolowski, 2006; Castro et al, 2015), while selected neuronal subpopulations of the NAc in the monkey are differently activated by cocaine and juice rewards (Bowman et al, 1996; Hutsell et al, 2016). All these data suggest that there are different and parallel microcircuits mediating the natural and drug-rewarding effects in the NAc (Alizamini et al, 2017; Faramarzi et al, 2016), although the relevant neurotransmitters have not been identified. Our results are consistent with the view that there are distinct neuronal populations within the NAc that mediate seeking behaviors for natural and drug rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the pain relief produced by an intrathecal injection of pregabalin in a model of spinal nerve ligation is accompanied by increase in the levels of NAc dopamine, and effect detected during the early but not during the late phase of the experimentally induced neuropathic pain ( Kato et al, 2016 ). Conversely, intra-accumbal infusions of D1- (SCH-23390) and D2-like (Sulpiride) dopamine receptors antagonists reduces stress-induced analgesia in a dose-dependent manner, in the early and late phases of an experimental model of persistent inflammatory pain, though with more pronounced effects found throughout the late phase ( Faramarzi et al, 2016 ).…”
Section: Molecular Targets At the Reward Circuitry For Pain Reliefmentioning
confidence: 99%
“…17 , 19 In modulation of pain and hyperalgesia, dopamine plays a major role in different areas of the brain including basal ganglia, 38 and it is one of the main sensitive pathways implicated in pain management. 39 Dopamine D1 receptor antagonist SCH-23,390 attenuate prostaglandin E2 (PGE 2 ) induced hyperalgesia and neuropathic allodynia. 40 Computationally, 4-FBS is a D1 receptor antagonist (support file 1) and it may be suggested that its anti-nociceptive, anti-allodynic activity is due to its antagonistic activity on the D1 receptor.…”
Section: Discussionmentioning
confidence: 99%